Cell Death - Autophagy, Apoptosis and Necrosis 2015
DOI: 10.5772/61196
|View full text |Cite
|
Sign up to set email alerts
|

Between Armour and Weapons — Cell Death Mechanisms in Trypanosomatid Parasites

Abstract: Among the pathogenic protozoa, trypanosomatids stand out due to their medical and economic impact, especially for low-income populations in tropical countries. Together, sleeping sickness, Chagas disease and leishmaniasis affect millions of humans and animals worldwide, yet are neglected by the pharmaceutical industry. The current drugs for trypanosomatid infections are limited and unsatisfactory, with severe side effects leading to reduced quality of life and, in several instances, to the abandonment of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 227 publications
0
5
0
Order By: Relevance
“…On the other hand, the increase in the number of labelled parasites was only induced by Pgd, indicating that only this compound promotes an increase in both the percentage of epimastigotes producing ROS and the quantity of reactive species generated. Lipid peroxidation is a classical consequence of the increase in cellular ROS amounts, which can also lead to plasma membrane rupture [ 15 ]. Our results showed an increase in plasma membrane permeability and ROS production only after incubation with Pgd, which is indicative of necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the increase in the number of labelled parasites was only induced by Pgd, indicating that only this compound promotes an increase in both the percentage of epimastigotes producing ROS and the quantity of reactive species generated. Lipid peroxidation is a classical consequence of the increase in cellular ROS amounts, which can also lead to plasma membrane rupture [ 15 ]. Our results showed an increase in plasma membrane permeability and ROS production only after incubation with Pgd, which is indicative of necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another biological pathway that has been associated with the mechanisms of action of anti-trypanosome drugs is autophagy [ 13 , 14 ]. The autophagy pathway is a pivotal degradation process in the recycling of cellular structures, which is also important in trypanosomatids [ 15 ]. The loss of autophagic balance could represent a critical point for the development of chemotherapeutic alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, much evidence has been accumulated to describe morphological and biochemical events displayed during the death of trypanosomatids which share certain characteristics with mammalian apoptosis phenomena (Debrabant et al, 2003;Fernandez-Presas et al, 2010;Menna-Barreto & Castro, 2015). The apoptotic features shown by these kinetoplastid parasites include DNA fragmentation, depolarization of mitochondrial membrane potential, protease activation, membrane blebbing, the exposure of phosphatidylserine in the outer leaflet of the plasma membrane, chromatin condensation and cytochrome c release.…”
Section: Discussionmentioning
confidence: 99%
“…Trypomastigotes may be prone to activate constant mechanisms of tolerance to cellular stress; therefore, UBMC-4 might act regardless of the parasites being subjected to nutritional stress or not. The second is a hypothesis that has already been proven in different studies where trypomastigotes are shown to be highly autophagic, a process known to have a dual function inhibiting or promoting apoptosis-mediated cell death processes [37].…”
Section: T Cruzi Is More Sensitive To Nutritional Stress In the Prese...mentioning
confidence: 98%